2005
DOI: 10.1521/pedi.2005.19.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Psychopathy Facets and Externalizing in a Criminal Offender Sample

Abstract: The construct of psychopathy is viewed as comprising distinctive but correlated affectiveinterpersonal and social deviance facets. Here, we examined these facets of Hare's Psychopathy Checklist-Revised (PCL-R) in terms of their associations with the externalizing dimension of adult psychopathology, defined as the common factor underlying symptoms of conduct disorder, adult antisocial behavior, alcohol use/abuse, and drug abuse, along with disinhibitory personality traits. Correlational analyses revealed a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
130
0
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 46 publications
16
130
0
9
Order By: Relevance
“…In addition, various studies have shown that psychopathic traits are not a unitary construct: i.e. that its dimensions are distinctly associated with behavioral criterion variables (Patrick et al, 2005;Hicks and Patrick, 2006) and regional brain function (Carré et al, 2013;Cohn et al, 2013). Indeed, we found that neural responses during fear acquisition were positively associated with GM and II psychopathic traits and negatively with CU psychopathic traits (Cohn et al, 2013).…”
Section: Introductionmentioning
confidence: 57%
“…In addition, various studies have shown that psychopathic traits are not a unitary construct: i.e. that its dimensions are distinctly associated with behavioral criterion variables (Patrick et al, 2005;Hicks and Patrick, 2006) and regional brain function (Carré et al, 2013;Cohn et al, 2013). Indeed, we found that neural responses during fear acquisition were positively associated with GM and II psychopathic traits and negatively with CU psychopathic traits (Cohn et al, 2013).…”
Section: Introductionmentioning
confidence: 57%
“…The explanation for this divergence in findings almost certainly lies in the distinction between the affectiveinterpersonal versus the antisocial deviance features of psychopathy. It is the latter features that reflect heightened externalizing tendencies, including aggression and impulsiveness (Patrick 2007;Patrick et al 2005). However, most EEG/ERP and brain imaging studies have not examined effects for these two components of psychopathy separately (for exceptions, see Laakso et al 2001;De Oliveira-Souza et al 2008).…”
Section: An Integrative Conceptual Framework For Interpreting Resultsmentioning
confidence: 99%
“…Conversely, Patrick, Cuthbert, and Lang (1994) found that the poor fear conditioning of psychopathic individuals was associated with the impulsive-antisocial (Factor 2) dimension and suggested that such deficits reflect a problem with the maintenance of neural representations, undermining the ability to associate fear with specific environmental events. Noting the association between Factor 2 and antisociality, substance abuse, suicidal behaviors, and heightened negative affect, Patrick, Hicks, Krueger, and Lang (2005) have linked this construct to a "general inhibitory diathesis" (p. 352) that seems to include difficulty inhibiting pre-potent affective states.…”
Section: Introductionmentioning
confidence: 99%